Preparation of porous TiO2 films by means of pulsed laser deposition for photocatalytic applications - Iwulska, Anna; Śliwiński, Gerard (Photonics Letters of Poland, 2011)
In this work the preparation and structure properties of porous thin films of TiO2 were investigated. The films were produced by means of the pulsed laser deposition technique using laser pulses at 266nm (10Hz) and at fluencies of 1–3.5J/cm2. The process was performed in vacuum using O2 buffer gas and films were deposited on the SiO2 glass or Si substrate. X-ray diffraction (XRD) and Raman analysis of the structure and chemical composition of the obtained samples confirmed the presence of both anatase and rutile phase. For the O2 pressure applied above 10-2 hPa, the anatase bands were observed and below this value, rutile bands dominated in the Raman spectra in agreement with XRD data. Full Text: PDF References B. Ohtani, "Photocatalysis A to Z—What we know and what we do not know in a scientific sense", J. Photochem. Photob. C: Photochem. Rev. 11, 157 (2010)[CrossRef] D. Robert, S. Malato, "Solar photocatalysis: a clean process for water detoxification", Sci. Tot. Envir. 291, 85 (2002)[CrossRef] A. Fujishima, T.N. Rao, D.A. Tryk, "Titanium dioxide photocatalysis", J. Photochem. Photobio. C: Photochem. Rev. 1, 1 (2000)[CrossRef] M.F. Brunell et al., "Photocatalytic behavior of different titanium dioxide layers", Thin Solid Films 515, 6309 (2007)[CrossRef] M. Terashima, N. Inoue, S. Kashiwabara, R. Fujimoto, "Photocatalytic TiO2 thin-films deposited by a pulsed laser deposition technique", Appl. Surf. Sci. 169-170, 535 (2001)[CrossRef] E. Kociołek-Balawajder, M. Szymczyk, Przemysł Chemiczny 86/12 (2007) D.A.H. Hanaor, Ch.C. Sorrell, "Review of the anatase to rutile phase transformation", J. Mater. Sci. 46, 855 (2011)[CrossRef] J.-H. Kim, S. Lee, H.-S. Im, "The effect of target density and its morphology on TiO2 thin films grown on Si(100) by PLD", Appl. Surf. Sc., 151 6 (1999)[CrossRef] F. Di Fonzo et al., "Hierarchically organized nanostructured TiO2 for photocatalysis applications", Nanotechnology, 20, 1 (2009)[CrossRef] R.W. Kelsall et al., Nanotechnologie, (Warszawa, PWN 2008) Y. Xu and M. Shen, "Fabrication of anatase-type TiO2 films by reactive pulsed laser deposition for photocatalyst application", J. Mater. Process. Technol. 202, 301 (2008)[CrossRef] P.M. Martin, Handbook of Deposition Technologies for Films and Coatings - Science, Science, Applications and Technology (Elsevier 2010). S. Yamamoto et al., ", Thin Solid Films 401, 88 (2001)[CrossRef] Y. Shen et al., "Investigation on properties of TiO2 thin films deposited at different oxygen pressures", Opt. and Las. Tech. 40, 550 (2008)[CrossRef] T. Tolke, A. Kriltz, A. Rechtenbach, "The influence of pressure on the structure and the self-cleaning properties of sputter deposited TiO2 layers", Thin Solid Films 518, 4242 (2010)[CrossRef] V. Stranak et al., "Formation of TiOx films produced by high-power pulsed magnetron sputtering", J. Phys. D: Appl. Phys. 41, 055202 (2008)[CrossRef]